PENGARUH MOTIVASI KERJA TERHADAP KINERJA KARYAWAN PT. TIGA ANGKASA PUTRA (BREAD STORY) - Daniel ,SE (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2013)
This study aims to analyze the influence of work motivation on employee performance PT Tiga Angkasa Putra (Bread Story). To determine how much influence the dependent variable (employee performance) with the independent variable (Physiological Needs, Sense of Security Requirements, Needs Socialization, Award Needs, Self Actualization). This study uses multiple regression analysis with SPSS version 17.0. This data collection method using a questionnaire to all employees of PT Tiga Angkasa Putra. Questionnaires were distributed 50 questionnaires. Results of studies using multiple linear regression analysis, showed that variable physiological needs (X1), Need for safety (X2), Needs Socialization (X3) Awards (X4), Self Actualization (X5) has a significant impact on employee performance (Y) . While partial, Needs socialization variables showed significant influence on employee performanceKeywords: Work motivation, Physiological Needs, Requirements sense of safety, socialization Need, Needs Respect, Self-Actualization Needs, and Performance.